PENGARUH GOOD CORPORATE GOVERNANCE, RASIO LIKUIDITAS, DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2018) - Angelicha Marsha Dewi; Silfi Alfiati; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aimed to examine the influence of good corporate governance, liquidity ratio and sales growth on financial distress. The mechanism of good corporate governance in this study include the number of boards of directors, proportion of independent board of commissioners, managerial ownership, and institutional ownership. The population taken in this study is a manufacturing company listed in the Indonesia Stock Exchange in the year 2016 to 2018. The data used in this study is secondary data, namely the Annual Financial Report. From the population obtained the total of samples of 37 companies which experiencing financial distress samples for 3 years. Data obtained by using purposive sampling method and the financial distress measured by using Altman Z-Score (1968). This study uses multiple regression analysis and was carried out using of the SPSS program ver. 25.0. The results of this study show that (1) the number of boards of directors affects financial distress, (2) proportion of independent board of commissioners affects financial distress, (3) managerial ownership affects financial distress, (4) institutional ownership affects financial distress, (5) liquidity ratio affects financial distress, (6) and sales growth affects financial distress.Keywords: The Number of Boards of Directors, Proportion of Independent Board of Commissioners, Manajerial Ownership, Institutional Ownership, Liquidity Ratio, Sales Growth. Financial Distress.